If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + y = 6y Solving 20 + y = 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 20 + y + -6y = 6y + -6y Combine like terms: y + -6y = -5y 20 + -5y = 6y + -6y Combine like terms: 6y + -6y = 0 20 + -5y = 0 Add '-20' to each side of the equation. 20 + -20 + -5y = 0 + -20 Combine like terms: 20 + -20 = 0 0 + -5y = 0 + -20 -5y = 0 + -20 Combine like terms: 0 + -20 = -20 -5y = -20 Divide each side by '-5'. y = 4 Simplifying y = 4
| 9=-h+5h+7 | | 74=2s+(6-2s) | | X+70=x+124 | | 9.35t=51.425 | | 5w^2-2w-1=0 | | 6x+3(0)=12 | | 35n+100=40n | | 40=2/3w | | 1/36-1/9x | | 2(x-6)=2x-10 | | 6(0)+3y=12 | | X+70+x+124=180 | | 5.2e=46.8 | | 1/236-1/9x | | X+17+x+124=180 | | 12.94=d-55.2 | | 3(u-2)= | | 27+x=100 | | 2x^4-x^3+9x^2-4x+4=0 | | 42.4=c+27.9 | | -42x^2-19x=0 | | ln(x+2)=2ln(x) | | 3/5d=-12 | | -5y+2(0)=-10 | | x^3-4x^2-20=-48 | | 15=12(5x+8) | | -4(m-2)=6m+5 | | Ab+c=b | | -114+7x=-2x+147 | | (v/8)-9=-13 | | -1/3-21/3 | | 5t(3-6t)= |